Recognition of insects possible associated in oil palm (Elaeis guineensis Jacq.) with lethal wilt disturbance - Morillo, Francy; Salazar G, Claudia; Tupaz V, Andrés; Oliveros D, Mauricio (Revista de Ciencias Agrícolas, 2012)
This study was carried out in order to recognize and identify the species diversity of insects of the order Hemiptera, suborder Auchenorryncha who visiting oil palm, possibly associa- ted with the spread of Lethal Wilt disturbance in lots of palm with different disease inci- dence. To analyze records were used diversity indices Shannon-Wiener, Simpson, Jaccard, Sorensen and Margalef. Using a hierarchical classification groups were formed with lots of species of greatest similarity. Results showed a total of 43.310 individuals belonging to 39 species located within 8 families, most insects were Auchenorrhyncha, both in number of species and individuals belonged to the family Cicadellidae (41.843 individuals and 28 species). In all lots predominated the Zyginama sp species (37.630 individuals in total). The species wealth and diversity were higher in lots of low incidence, the species similarity was greater between lots with average incidence versus low disease incidence. Zyginama sp ob- tained the highest frequency and density of population with 90.11% and 86.9% respectively. The hierarchical classification showed the formation of two groups characterized by the species similarity, including the group 1 formed by lots of young palm with middle and low disease incidences, with the largest number of species and individuals recorded. Group 2 formed by four adult lots of low and middle incidence and a healthy lot of the disease. In survival tests was found that Zyginama sp in its adult stage feeds of oil palm.